2015
DOI: 10.1161/circulationaha.114.013876
|View full text |Cite
|
Sign up to set email alerts
|

Cinacalcet, Fibroblast Growth Factor-23, and Cardiovascular Disease in Hemodialysis

Abstract: Background-Patients with kidney disease have disordered bone and mineral metabolism, including elevated serum concentrations of fibroblast growth factor-23 (FGF23). These elevated concentrations are associated with cardiovascular and all-cause mortality. The objective was to determine the effects of the calcimimetic cinacalcet (versus placebo) on reducing serum FGF23 and whether changes in FGF23 are associated with death and cardiovascular events. Methods and Results-This was a secondary analysis of a randomiz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
125
1
3

Year Published

2016
2016
2018
2018

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 274 publications
(134 citation statements)
references
References 33 publications
5
125
1
3
Order By: Relevance
“…FGF23 concentrations were reduced by ≥50% in 50% versus 15% in patients randomized to cinacalcet versus placebo, respectively. 91 By week 20, neutralization of FGF23 was associated with a significantly reduced risk of cardiovascular mortality, SCD, and heart failure and in the primary composite end point (ie, time to death or a first nonfatal cardiovascular event [myocardial infarction, hospitalization for angina, heart failure, or a peripheral vascular event]). Reductions in the risk of all-cause mortality, myocardial infarction, unstable angina, peripheral vascular event, stroke, fracture, and parathyroidectomy were not statistically significant.…”
Section: Fibroblast Growth Factor-23-klotho Signaling Axismentioning
confidence: 99%
“…FGF23 concentrations were reduced by ≥50% in 50% versus 15% in patients randomized to cinacalcet versus placebo, respectively. 91 By week 20, neutralization of FGF23 was associated with a significantly reduced risk of cardiovascular mortality, SCD, and heart failure and in the primary composite end point (ie, time to death or a first nonfatal cardiovascular event [myocardial infarction, hospitalization for angina, heart failure, or a peripheral vascular event]). Reductions in the risk of all-cause mortality, myocardial infarction, unstable angina, peripheral vascular event, stroke, fracture, and parathyroidectomy were not statistically significant.…”
Section: Fibroblast Growth Factor-23-klotho Signaling Axismentioning
confidence: 99%
“…A broad face is usually associated with a brachycephal and similarly a long face is associated with long head or dolichocephalic. Though this is a harmonic relation between the head and the face, but not universal in occurrence [82]. For example, the Armenoids (a subtype of Caucasoid ancestry) who possess long and relatively narrow faces along with relatively short and broad heads.…”
Section: Upper Facial Indexmentioning
confidence: 99%
“…The modern people are generally orthognathous, only a few of them may show a little prognathism. Among the human population, the Mongoloids and some white people show slight or moderate alveolar prognathism but facial prognathism is almost absent in them [82].…”
Section: Gnathic Indexmentioning
confidence: 99%
“…Sixty-four percent of patients assigned to cinacalcet had $30% reduction in serum FGF-23 concentrations from baseline to week 20 compared with 28% of the placebo group (29). Among patients randomly assigned to cinacalcet, a $30% reduction in FGF-23 was associated with a significant reduction in the composite CV end point (relative hazard, 0.82; 95% CI, 0.69 to 0.98) (29). This nonrandomized analysis generates the hypothesis that FGF-23 plays a role in the pathogenesis of CV events in CKD and the deleterious effects of FGF-23 might be ameliorated by cinacalcet.…”
Section: Biomarkersmentioning
confidence: 99%
“…From 2007 to 2011, accumulating data in patients with advanced CKD and ESRD showed that serum fibroblast growth factor-23 (FGF-23) concentrations were elevated and were associated with mortality, left ventricular hypertrophy, and CV events independent of serum phosphate, PTH, and a variety of demographic and other clinical factors (27,28). Sixty-four percent of patients assigned to cinacalcet had $30% reduction in serum FGF-23 concentrations from baseline to week 20 compared with 28% of the placebo group (29). Among patients randomly assigned to cinacalcet, a $30% reduction in FGF-23 was associated with a significant reduction in the composite CV end point (relative hazard, 0.82; 95% CI, 0.69 to 0.98) (29).…”
Section: Biomarkersmentioning
confidence: 99%